FAKTOR YANG BERHUBUNGAN DENGAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS DONGGO KABUPATEN BIMA TAHUN 2020 - Hamdin Hamdin; Abdul Hamid (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Chronic Energy Deficiency is a condition of pregnant women who suffer from chronic (regular) food shortages, resulting in health problems for pregnant women, indicated by the size of the upper arm circumference <23.5 cm. The purpose of this study was to determine the factors associated with chronic energy deficiency in pregnant women in the work area of the Donggo Public Health Center, Kab. Bima includes: This type of research uses a Cross-Sectional Study. Determination of the sample using the method of accidental random sampling. Data were obtained from pregnant women who came to check on the ongoing research. Data processing uses a computerized system with Odds Ratio analysis. The results showed a relationship between maternal knowledge, Pregnancy Distance, Frequency of eating , Food Intake, and the incidence of CED in pregnant women. The conclusion of this study shows a relationship between knowledge, gestational distance, frequency of eating, food intake, and the incidence of CED in pregnant women. Suggestions that can be given are to provide counseling about the dangers of SEZ to pregnant women, knowledge of the importance of nutrition, and pregnancy check-ups by health workers.